Co-expression of Leptin and Leptin Receptor in Adenocarcinoma of the Colon in Malay Population - Abdulrazzaq, Saad Mohammed; Harun, Norra; Al-Kubaisi, Muna Khaleel Dheyab (2020)
Objectives: To assess the role of leptin in human colonic adenocarcinoma and to establish its expression in Malay population patients by using immunohistochemistry study. Methodology: Immunohistochemical study (IHC) using antibodies against leptin and its receptor was applied to assess the expression of leptin and its receptor in 38 samples of adenocarcinoma of the colon among Malay population and compare this expression with that of the adjacent normal colon tissue. Results: All the 38 colon adenocarcinoma samples stained strongly (100%) for leptin and 36 out of 38 also stained strongly for leptin receptor (95%). The other 2 (5%) stained weak (1+). However, the whole specimens of the normal adjacent colon tissue stained weakly (1+) for both leptin and leptin receptor. The expression of both hormones in cancer and normal tissue is significantly different (p<0.01). There was significant co-expression of both hormones in colonic cancerous tissue. Conclusions: Leptin/leptin receptor system may have a tumorigenic effect on the colon tissue, most likely by an autocrine process. Inhibition of leptin/leptin receptor system might be helpful in the prevention and management of colon cancer.